Determination of Mizaj (Temperament) in women with mixed urinary incontinence: A preliminary study: A. Sultan, A. G. F. Najeeya, K. Rahman, M. U. Z. N. Farzana (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2021)
Mixed urinary incontinence (MUI) has been defined symptomatically by the International Continence Society as ‘‘the complaint of involuntary leakage associated with urgency and also with exertion, effort, sneezing or coughing.’’ One of the fundamental concepts of Unani system of medicine is Mizaj. Mizaj of the organ/body may be affected by internal and external factors leading to Su’-i-Mizaj, causes disease. Some of the causes of Salas al-Bawl are Su’-i-Mizaj Barid, Zo’fe Mathana, Mudirr-i-Bawl, Khala Faqra, alcohol, excessive fluid intake, or injury to Adala al-Mathana. Therefore, evaluation of Mizaj of an individual or organ is important for treatment of the disease. Thus, this study was conducted to determine the Mizaj in women with MUI. A prospective, single centre preliminary study was conducted in 60 women diagnosed with MUI from February 2015 to June 2015 at the National Institute of Unani medicine, India. Questionnaire for assessment of Women’s general Mizaj (based on Alamat AjnaseAshra) was used. Further, Alamat Su’-i-Mizaj (clinical features of abnormal temperament) of body as described in the traditional Unani literature were used to assess the Su’-i-Mizaj. The data was analyzed by descriptive analysis using Graph pad. Of 60 patients, 43(71.66%), 2(3.33%) and 15(25%) patients had Barid, Harr and Motadil general Mizaj respectively. Of 60 patients, 13(21.66%), 25(41.66%) and 22(36.66%) patients had Yabis, Ratb and Motadil general Mizaj respectively. Of 60 patients, 56(93.33%), and 4(6.66%) patients had Barid,and Harr Su’-i-Mizaj respectively. This preliminary study validated the claim of Unani scholars that this disease is more common in Barid Mizaj and the Su’-i-Mizaj is towards Burudat in women with MUI. 1National Institute of Unani Medicine, Bangalore, Karnataka, India 2Kegalle Ayurvedic Hospital, Sri Lanka 3Institute of Indigenous Medicine, University of Colombo, Rajagiriya, Sri Lanka *Correspondence: A. Sultana, Associate Professor, Department of Amraze Niswan wa Ilmul Qabalat (Gynecology and Obstetrics), National Institute of Unani Medicine, Bangalore, Karnataka, India. Email: drarshiya@yahoo.com; drasnium@gmail.com